Reproductive biology of female bigeye tuna Thunnus obesus in the western Pacific Ocean. Issue 2 (1st July 2013) - Sun, C. L.; Yeh, S. Z.; Chang, Y. J.; Chang, H. Y.; Chu, S. L.
Abstract : The reproductive biology of female bigeye tuna Thunnus obesus was assessed by examining 888 fish (ranging from 84·9 to 174·4 cm fork length, L F ) caught by Taiwanese offshore longliners in the western Pacific Ocean from November 1997 to November 1998 and November to December 1999 and 258 gonad samples from these fish. The overall sex ratio of the catch during the sampling differed significantly from 0·5, but males were predominant in sizes >140 cm L F . Reproductive activity (assessed by histology), a gonado‐somatic index, and the size‐frequency distributions of whole oocytes indicated that spawning occurred throughout the year and the major spawning season appeared to be from February to September. The estimated sizes at 50% maturity ( L F50 ) of females was 102·85 cm (95%c.i .: 90·79–110·21 cm) and the smallest mature female was 99·7 cm L F . They are multiple spawners and oocytes develop asynchronously. The proportion of mature (0·63) and reproductively active (0·70) females with ovaries containing postovulatory follicles indicated that they spawn almost daily. Batch fecundity for 15 females with the most advanced oocytes (>730 µm) ranged from 0·84 to 8·56 million eggs (mean ± s.d . = 3·06 ± 2·09). The relationships between batch fecundity ( F B, in millions of eggs) and L F (cm) and round mass ( M R, kg) were F B = 9 · 91 × 1 0 − 14 L F 6 · 38 ( r 2  = 0·84) and F B = 8 · 89 × 1 0 − 4 M R 2 · 05 ( r 2  = 0·80), respectively. The parameters estimated in this study are key information for stock assessments of T. obesus in the western Pacific Ocean and will contribute to the conservation and sustainable yield of this species.